Disputation of Doctor Martin Luther on the power and efficacy of indulgences - Luther, Martin 1483-1546 (Project Gutenberg, 1990)
The German Reformation leader Martin Luther (1483-1546) wrote the theses "Disputation of Doctor Martin Luther on the Power and Efficacy of Indulgences," in 1517. The text is provided online by Central Valley Christian School. Martin Luther was excommunicated because of these ideas.
Access may be limited to NetLibrary affiliated libraries
Keywords: Luther, Martin -- 1483-1546; Luther, Martin -- 1483-1546 -- Thesen; Central Valley Christian School; Luther, Martin (German Reformation leader); Thesenanschlag; Electronic publications; Reformation; Reformation -- Germany; Theologie; Ablassstreit; Polemik; Gnade; Ablass; Deutschland; Electronic books; Patentschrift